Addition of lidocaine to levobupivacaine reduces intrathecal block duration: randomized controlled trial - Yazicioglu,Dilek (2014)
Background: The duration of the spinal block is a concern for anesthetists. Low dose intrathecal lidocaine has vasodilatory effects and increases the local anesthetic clearance from the intrathecal space. The aim was to investigate whether this effect of lidocaine can be used to increase the resolution of levobupivacaine spinal anesthesia. Method: After obtaining ethical approval and informed patient consent, 40 patients underwent transurethral prostate resection were studied. Patients were randomized into two groups and patients received either levobupivacaine 6.75 mg + 0.3 mL 2% lidocaine (Group L) or levobupivacaine 6.75 mg + saline (Group C). The main outcome measures were the difference between groups regarding the duration of the spinal block and PACU stay. Secondary outcome measures were the difference between groups in onset and resolution of the spinal block, adverse events and treatments were also investigated. Results: Spinal block resolved faster in Group L than Group C; 162.43 ± 39.4 min vs 219.73 ± 37.3 min (p = 0.000). PACU time was shorter in Group L (109 ± 49.9 min in Group L vs 148 ± 56.8 min in Group C) (p = 0.036). There was no difference between groups with respect to the incidence of adverse events and treatments. Groups were also similar regarding complications. PDPH and TNS were not observed in any group. Conclusion: Addition of low dose lidocaine to hyperbaric levobupivacaine reduces the duration of the intrathecal block provided by hyperbaric levobupivacaine. This technique can be used to reduce the spinal block duration for relatively short procedures like TUR-P.